Assessing models of speciation under different biogeographic scenarios; an empirical study using multi‐locus and RNA‐seq analyses. Issue 2 (7th January 2016) - Edwards, Taylor; Tollis, Marc; Hsieh, PingHsun; Gutenkunst, Ryan N.; Liu, Zhen; Kusumi, Kenro; Culver, Melanie; Murphy, Robert W.
Abstract: Evolutionary biology often seeks to decipher the drivers of speciation, and much debate persists over the relative importance of isolation and gene flow in the formation of new species. Genetic studies of closely related species can assess if gene flow was present during speciation, because signatures of past introgression often persist in the genome. We test hypotheses on which mechanisms of speciation drove diversity among three distinct lineages of desert tortoise in the genus Gopherus . These lineages offer a powerful system to study speciation, because different biogeographic patterns (physical vs. ecological segregation) are observed at opposing ends of their distributions. We use 82 samples collected from 38 sites, representing the entire species' distribution and generate sequence data for mtDNA and four nuclear loci. A multilocus phylogenetic analysis in *BEAST estimates the species tree. RNA‐seq data yield 20, 126 synonymous variants from 7665 contigs from two individuals of each of the three lineages. Analyses of these data using the demographic inference package ∂a∂i serve to test the null hypothesis of no gene flow during divergence. The best‐fit demographic model for the three taxa is concordant with the *BEAST species tree, and the ∂a∂i analysis does not indicate gene flow among any of the three lineages during their divergence. These analyses suggest that divergence among the lineages occurred in the absence of gene flow and in this scenario the genetic signature of ecological isolation (parapatric model) cannot be differentiated from geographic isolation (allopatric model). Abstract : We present an empirical study on speciation and examine the relative importance of isolation and gene flow in the formation of new species. Our taxa of interest, desert tortoise in the genus Gopherus, provides a powerful system to study speciation because different biogeographic patterns (physical vs. ecological segregation) are observed at opposing ends of the distribution of three distinct desert tortoise lineages. Our findings suggest that the genetic signature of ecological isolation (parapatric model) cannot be differentiated from geographic isolation (allopatric model).